(untitled) (Research, Society and Development, 2023)
The objective of this study is to understand how psychology can contribute to listening to children who are victims of sexual violence, considering the phenomenon of false memories, their repercussions and the instruments that this professional can use in carrying out this procedure. This is an integrative literature review with a qualitative approach. For the elaboration of this study, the articles were searched in the Periódicos Capes portal and in the Scientific Electronic Library Online (Scielo) database. The results indicate that, based on studies carried out, false memories can be autonomous and suggested, and can be influenced by both internal and external factors from the environment. It was possible to analyze that in Brazil, some of the instruments used by psychologists to assist in their practice are the Cognitive Interview, the NICHD protocol (National Institute Child and Human Development) and the Forensic Interview Protocol. It is concluded that the psychology professional has been increasingly requested in special testimony procedures, due to the need for continued training through instruments recognized by psychological science. As found in this study, I refer to the few surveys carried out in the established time lapse, giving rise to new studies that address the prevalence of false memories in the reports of victims of violence, considering the risks and challenges of this phenomenon, with a view to further improving techniques used in listening to children and adolescents.